1983
DOI: 10.1182/blood.v62.2.473.473
|View full text |Cite
|
Sign up to set email alerts
|

Delayed alloimmunization using random single donor platelet transfusions: a prospective study in thrombocytopenic patients with acute leukemia

Abstract: A randomized study was performed in 54 thrombocytopenic patients with acute leukemia. Alloimmunization of recipients of random multiple-donor platelet concentrates (MD group) was compared to that of patients receiving random single-donor platelets (SD group). In the SD patients, formation of alloantibodies (mostly anti-HLA) occurred less frequently (p less than 0.002), after a longer time period (p less than 0.002), and after a higher number of transfusions (p less than 0.005) as compared to MD patients. SD pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This trend has resulted from the observations that SDPs Pearson correlation indicates good correlation between predonation platelet count and yield for all procedures (r ¼ 0.51, P < 0.001). are a better platelet product due to less donor exposures and consequent reduction in transfusion transmitted diseases (Goodnough et al, 1999a,b), transfusion reactions (Chambers et al, 1990) and possibly alloimmunization (Gmur et al, 1983). Currently, more than 50% of platelets are produced by plateletpheresis in developed countries (Wallace et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This trend has resulted from the observations that SDPs Pearson correlation indicates good correlation between predonation platelet count and yield for all procedures (r ¼ 0.51, P < 0.001). are a better platelet product due to less donor exposures and consequent reduction in transfusion transmitted diseases (Goodnough et al, 1999a,b), transfusion reactions (Chambers et al, 1990) and possibly alloimmunization (Gmur et al, 1983). Currently, more than 50% of platelets are produced by plateletpheresis in developed countries (Wallace et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…using only single-donor platelets, prophylactic HLA-matching, and leukoreduction or irradiation of cellular blood products. The use of prophylactic single-donor platelets to reduce HLA alloimmunization by reducing foreign antigen exposure was examined in several clinical studies (36,37) including a prospective randomized trial (38). While some studies supported such practice, others failed to show a consistent benefit and the practice is not generally recommended.…”
Section: Prevention Of Hla Alloimmunizationmentioning
confidence: 99%
“…We did not find a statistically significant association between the number of cellular transfusions and alloimmunisation (P = 0·38). Most transfusion trials on humans suggest that there is a dose-response relationship between the number of exposures and the risk of alloimmunisation (Gmur et al, 1983). However, there was an absence of dose-response relationships for the development of alloantibodies by a study conducted by (Dutcher et al (1981) The study also demonstrated that the rate of immunisation is independent of the number of platelet units transfused.…”
Section: Discussionmentioning
confidence: 97%